Multi-platform observations and constraints reveal overlooked urban sources of black carbon in Xuzhou and Dhaka - Pravash Tiwari; Jason Blake Cohen; Lingxiao Lu; Shuo Wang; Xiaolu Li; Luoyao Guan; Zhewen Liu; Zhengqiang Li; Kai Qin (Communications Earth & Environment)
Abstract Here we use multi-waveband single scattering albedo observations from ground-based instruments and satellite to constrain black carbon aerosol's physical properties and loading over Xuzhou, China, and Dhaka, Bangladesh. Our daily high-resolution findings reveal smaller black carbon cores and spatially variable morphology dominate both regions. Column loadings reveal higher black carbon mass in Dhaka, while higher total aerosol mass and number are observed in Xuzhou. These findings reflect differences in emission sources, atmospheric conditions, and regulatory policies. Spatial analysis reveals notable enhanced black carbon along Dhaka’s urban riverbanks (8–9 mg m−2), and over rapidly changing, small industrial sites in China, indicating overlooked sources. Complex daily interactions between wind, accumulation, and dispersion challenge traditional seasonal dynamics. These findings demonstrate high-resolution data can be tailored from available remote sensing platforms, providing nuanced insights into regional air quality, enhancing assessment capabilities and informing targeted mitigation strategies.